(untitled) (Research, Society and Development, 2021)
Non-carious cervical lesions affect numerous people annually, causing pain and discomfort due to the presence of dental hypersensitivity. This study aimed to compare the effectiveness of laser therapy XT® irradiation with Clinpro White Varnish fluoride varnish, through a clinical trial in hemi-arches, based on the scores obtained by the visual analogue scale. The patient had intolerable pain (10) on teeth 14, 15, 45, 24, 25 and 34 and tolerable severe pain (8) on teeth 26, 27, 43 and 44, for the thermal, evaporative, and tactile tests. The varnish was applied once to teeth 14, 15, 43, 44 and 45. In the 1st week the scores 10 and 8 dropped to 3 (moderate/bearable pain). In the 2nd week, sensitivity remained between 3 and 1, with 1 being mild pain and in the 3rd week between 0 and 1, with 0 being no pain. Therapeutic laser was applied to teeth 24, 25, 26, 27 and 34. In the 1st week there was a decrease in the score 10 and 8 to 5 (moderate pain, but with discomfort). In the 2nd week, this score dropped to 3 (moderate/bearable pain) and remained in the 3rd week, with variations between 3 and 1 (presence of mild pain). Only in the 4th week there was a decrease in sensitivity, with a score between 1 and 0 (no pain) for the different stimuli. Both treatments were effective in reducing dentin sensitivity, however, with different action times between the two products, respecting their individual characteristics and properties.